Budaya Mulukade Sebagai Media Pelayanan Pastoral Konseling Dalam Kedukaan Di GMIST Jemaat Imanuel Ondong - Katiandagho, Okdita Lekungbulaeng; Weol, Wolter (PT. Giat Konseling Nusantara, 2024)
Mulukade culture is the culture of the people of North Nusa, especially siau, which is carried out from the past to the present. If there is a family that experiences a mourning event, then all members of the community / congregation are present to accompany the bereaved family, by taking turns singing and singing all night or until morning to comfort and strengthen the bereaved family. This article aims so that Mulukade culture as the heritage of the ancestors will not lose its usefulness but can be preserved, besides that Mulukade culture can be developed as a medium for Pastoral Counseling services for members of the community / congregation who are grieving. The research was carried out using a qualitative method at GMIST Imanuel Ondong Congregation. Budaya Mulukade adalah budaya masyarakat Nusa Utara khususnya siau yang dilakukan dari dahulu hingga sekarang ini. Apabila ada keluarga yang mengalami peristiwa dukacita, maka semua anggota masyarakat / jemaat hadir mendampingi keluarga yang berduka, dengan mengangkat nyanyian secara bergantian dan menyanyi semalaman atau sampai pagi untuk menghibur dan menguatkan keluarga yang berduka. Artikel ini bertujuan agar budaya Mulukade sebagai warisan para leluhur tidak akan hilang mamfaatnya tetapi dapat dilestarikan, selain itu budaya Mulukade dapat dikembangkan sebagai media pelayanan Pastoral Konseling bagi anggota masyarakat / jemaat yang berdukacita. Penelitia dilakukan dengan metode kualitatif di GMIST Jemaat Imanuel Ondong.